LSP5-2157 a new inhibitor of vesicular glutamate transporters. (1st March 2020) - Poirel, Odile; Mamer, Lauren E.; Herman, Melissa A.; Arnulf-Kempcke, Marie; Kervern, Myriam; Potier, Brigitte; Miot, Stephanie; Wang, Jing; Favre-Besse, Franck-Cyril; Brabet, Isabelle; Laras, Younès; Bertrand, Hugues-Olivier; et al.
Abstract: Vesicular glutamate transporters (VGLUT1-3) mediate the uptake of glutamate into synaptic vesicles. VGLUTs are pivotal actors of excitatory transmission and of almost all brain functions. Their implication in various pathologies has been clearly documented. Despite their functional importance, the pharmacology of VGLUTs is limited to a few dyes such as Trypan Blue, Rose Bengal or Brilliant Yellow type. Here, we report the design and evaluation of new potent analogs based on Trypan Blue scaffold. Our best compound, named LSP5-2157, has an EC50 of 50 nM on glutamate vesicular uptake. Using a 3D homology model of VGLUT1 and docking experiments, we determined its putative binding subdomains within vesicular glutamate transporters and validated the structural requirement for VGLUT inhibition. To better estimate the specificity and potency of LSP5-2157, we also investigated its ability to block glutamatergic transmission in autaptic hippocampal cells. Neither glutamate receptors nor GABAergic transmission or transmission machinery were affected by LSP5-2157. Low doses of compound reversibly reduce glutamatergic neurotransmission in hippocampal autpases. LSP5-2157 had a low and depressing effect on synaptic efficacy in hippocampal slice. Furthermore, LSP5-2157 had no effect on NMDA-R- mediated fEPSP but reduce synaptic plasticity induced by 3 trains of 100 Hz. Finally, LSP5-2157 had the capacity to inhibit VGLUT3-dependent auditory synaptic transmission in the guinea pig cochlea. In this model, it abolished the compound action potential of auditory nerve at high concentration showing the limited permeation of LSP5-2157 in an in-vivo model. In summary, the new ligand LSP5-2157, has a high affinity and specificity for VGLUTs and shows some permeability in isolated neuron, tissue preparations or in vivo in the auditory system. These findings broaden the field of VGLUTs inhibitors and open the way to their use to assess glutamatergic functions in vitro and in vivo .